Auxin and cytokinin relationships in 24 microalgal strains1. Issue 3 (3rd April 2013) - Stirk, Wendy A.; Ördög, Vince; Novák, Ondřej; Rolčík, Jakub; Strnad, Miroslav; Bálint, Péter; van, Johannes; Bassi, R.
<x xml:space="preserve">Abstract</x> Endogenous auxins and cytokinins were quantitated in 24 axenic microalgal strains from the Chlorophyceae, Trebouxiophyceae, Ulvophyceae, and Charophyceae. These strains were in an exponential growth phase, being harvested on day 4. Acutodesmus acuminatus Mosonmagyaróvár Algal Culture Collection‐41 (MACC) produced the highest biomass and Chlorococcum ellipsoideum MACC‐712 the lowest biomass. The auxins, indole‐3‐acetic acid (IAA) and indole‐3‐acetamide (IAM) were present in all microalgal strains. No other auxin conjugates were detected. IAA and IAM concentrations varied greatly, ranging from 0.50 to 71.49 nmol IAA · g−1 DW and 0.18 to 99.83 nmol IAM · g−1 DW, respectively. In 19 strains, IAA occurred in higher concentrations than IAM. Nineteen cytokinins were identified in the microalgal strains. Total cytokinin concentrations varied, ranging from 0.29 nmol · g−1 DW in Klebsormidium flaccidum MACC‐692 to 21.40 nmol · g−1 DW in Stigeoclonium nanum MACC‐790. The general trend was that cis‐zeatin types were the predominant cytokinins; isopentenyladenine‐type cytokinins were present in moderate concentrations, while low levels of trans‐zeatin‐type and very low levels of dihydrozeatin‐type cytokinins were detected. Ribotides were generally the main cytokinin conjugate forms present with the cytokinin free bases and ribosides present in similar but moderate levels. The levels of O‐glucosides were low. Only one N‐glucoside was detected, being present in nine strains in very low concentrations. In 15 strains, the auxin content was 2‐ to 4‐fold higher than the cytokinin content.